Bibliometric Analysis of Cooperatives Role in a Environmental Economy - Kamalia, Putri Ulfa; Subroto, Waspodo Tjipto; Sakti, Norida Canda (CV. Science Tech Group, 2025)
This study aims to analyze the development trends and direction of research on the role of cooperatives indexed in Scopus from 2014 to 2024. This type of research is quantitative research using bibliometric analysis. Based on the search results, there are 149 research articles, then inputted into the VOSviewer application and analyzed descriptively through a literature review study. The results showed that the number of publications has increased every year. Then, based on the mapping results using the VOSviewer application, research on the role of cooperatives is divided into 13 clusters. Meanwhile, based on the results of the literature review study, there are 7 main themes around the role of cooperatives. Recent trends show increased attention to environmental issues and adjustment to change. The practical implication of this research is the need to strengthen cooperative management through innovation in various fields, such as technology, education and the environment. Then for potential research directions to be developed in the future is research that includes keywords of agricultural cooperatives, cooperative interaction, cooperative learning, cooperative assembly, cooperative extension, SMES and environmental cooperatives variables because they are still rarely researched.